2017
DOI: 10.3390/app7080838
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polishing-Induced Subsurface Impurity Defects on Laser Damage Resistance of Fused Silica Optics and Their Removal with HF Acid Etching

Abstract: Laser-induced damage on fused silica optics remains a major issue that limits the promotion of energy output of large laser systems. Subsurface impurity defects inevitably introduced in the practical polishing process incur strong thermal absorption for incident lasers, seriously lowering the laser-induced damage threshold (LIDT). Here, we simulate the temperature and thermal stress distributions involved in the laser irradiation process to investigate the effect of impurity defects on laser damage resistance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 43 publications
(39 reference statements)
1
6
0
Order By: Relevance
“…Compared with the gray dotted line in Fig. 3(c), the tendency of our temperature curve with 355 nm wavelength is similar to the results calculated by Cheng et al 45 By changing laser irradiation sites, the temperature of the center is consistently very high under the stable-state calculation. Therefore, we can find that the center of the front surface is more possible to get damage caused by high temperature.…”
Section: Temperature and Thermal Stress Distributionsupporting
confidence: 89%
“…Compared with the gray dotted line in Fig. 3(c), the tendency of our temperature curve with 355 nm wavelength is similar to the results calculated by Cheng et al 45 By changing laser irradiation sites, the temperature of the center is consistently very high under the stable-state calculation. Therefore, we can find that the center of the front surface is more possible to get damage caused by high temperature.…”
Section: Temperature and Thermal Stress Distributionsupporting
confidence: 89%
“…Pápa et al showed an increasing trend up to 10 min by HF (38%), followed by a constant trend upto 20 min . Cheng et al reported a periodic trend of increasing–decreasing–increasing in the surface roughness of fused silica etched by a mixture of 5% HF and 10% NH 4 F, over 80 min . Koga et al observed a reduction in the surface roughness in the first 15 min of etching and a slow increment in the etching times greater than 20 min when using HF (5%) for etching the soda–lime glass surface .…”
Section: Resultsmentioning
confidence: 99%
“…54 Cheng et al reported a periodic trend of increasing−decreasing− increasing in the surface roughness of fused silica etched by a mixture of 5% HF and 10% NH 4 F, over 80 min. 55 Koga et al observed a reduction in the surface roughness in the first 15 min of etching and a slow increment in the etching times greater than 20 min when using HF (5%) for etching the soda−lime glass surface. 56 Therefore, the trend of roughness variation with etching time is not specific and depends on several parameters such as surface composition, HF concentration, and etching time.…”
Section: Effect Of the Etching Timementioning
confidence: 99%
“…A detailed study on the impact of subsurface impurity defects introduced in the polishing process of fused-silica optics, and the beneficial effect of HF acid etching in the defect removal and laser-induced damage threshold enhancement, is presented by J. Cheng, J. Wang, J. Hou, H. Wang, and L. Zhang in [10].…”
Section: Solid State Lasers Materials Technologies and Applicationsmentioning
confidence: 99%